Efficient Capital Market Theory and its Implications for Investment Decision Making in Financial Markets - Manao, Alwinda; Waspada, Ikaputera; Sari, Maya (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The Efficient Capital Market (ECM) theory is an important foundation in the understanding of modern financial markets, which states that asset prices reflect all available information. This article aims to analyze the implications of ECM on investment decision-making, as well as explore the differences between passive and active investment strategies in the context of an efficient market. The method used is a literature review, which includes an analysis of previous research results on market efficiency and investor behavior. The results of the Efficient Capital Market (ECM) Theory study have a significant impact on investment decision-making in financial markets. By understanding that asset prices reflect all available information, both public and private, investors can be more prudent in choosing the right investment strategy. In an efficient market, passive investment approaches, such as index funds, are often more profitable compared to active strategies, given their lower costs and more manageable risks. The implications of these findings emphasize the importance of investors' understanding of ECM principles, which can help them adopt more rational and data-driven strategies, and avoid decisions influenced by emotions. Thus, ECM is not only an academic theory, but also a practical guide to improve investment decision-making in financial markets.